(3HgLI GdfahSs - (3CHh eMeO YHO Gddg Hf SYO Hf CHi LeQI GdCROis; (3CHh eMeO YHO Gddg Hf SYO Hf CHj LeQI GdGROj,J (B695 (3g` s ((3CMHjH Hf eMeO fH eMeO GdedbH HQje s)
(3ChdgG (B:s
(3Yf YHO Gddg bGd (B: (3bGd c QShd Gddg Udi Gddg Ydjg hSde (B: (3ef Mda Ydi jejf hgh aGLQ djbWY HgG eGd GeQF eSde dbi Gddg hgh Ydjg ZVHGf s
(3BNQgG (B:s
(3Yf CHj SYjO GdNOQi Ef Gddg jbhd dCgd GdLfI (B: (3jG Cgd GdLfI , ajbhdhf (B: (3dHjc hSYOjc Gddge CfJ effJ Ydi HgPG GdTQM , hCNHQJfi Hg ai Gdfhe Cfc CNHQJ Hg BOe bHd ehJg , aGLYdg di fhQkG ai GdOfjG hGdBNQg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI cJHgG fGSNgG dCNjI ai Gddg eMeO Hf eMeO Hf GdCejf Hf ehO eGdc s
(3fSNI eQbeI GdChQGb s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs